2017
DOI: 10.1002/app.46037
|View full text |Cite
|
Sign up to set email alerts
|

Starch‐graphene oxide bionanocomposites prepared through melt mixing

Abstract: Bionanocomposites (BNCs) of waxy corn starch, glycerol, and graphene oxide (GO) or graphite oxide (GrO) were prepared by melt mixing. First, the GrO was pre-exfoliated in a water solution using ultrasound at 1 wt %. Small-angle X-ray scattering was used to determinate the interlaminar separation of GrO and transmission electron microscopy, Fourier infrared spectroscopy, and thermogravimetric analysis were used to characterized the GrO. Next, BNCs were characterized by X-ray diffraction, scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…As a consequence of this compatibility, hydrogen bond interactions can be formed between GO nanoplatelets and other phases, which lead to a more efficient stress transfer from matrix to CNF and GO nanoplatelets. Hence, the tensile strength further increases by incorporation of GO nanoplatelets . Another reason for this enhancement can be the good dispersion of GO nanoplatelets inside the matrix, which was shown by the XRD patterns in previous section and also the elongation behavior that is presented in Figure .…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…As a consequence of this compatibility, hydrogen bond interactions can be formed between GO nanoplatelets and other phases, which lead to a more efficient stress transfer from matrix to CNF and GO nanoplatelets. Hence, the tensile strength further increases by incorporation of GO nanoplatelets . Another reason for this enhancement can be the good dispersion of GO nanoplatelets inside the matrix, which was shown by the XRD patterns in previous section and also the elongation behavior that is presented in Figure .…”
Section: Resultsmentioning
confidence: 65%
“…Tensile strength and Young modulus of samples with 0.5 wt% of GO content increased by about 140% and 230%, respectively. Their results indicated that exfoliated GO avoided the retrogradation of starch . These results show that GO is highly compatible with thermoplastic starch.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The latter has also been demonstrated for the manufacture of biocomposites with graphite oxide where the ultrasonic oscillations were used to exfoliate the GrO on the surface of the starch granules, which were further melt blended to obtain PNCs with excellent mechanical properties [57]. Table 1 enlists some operating conditions of the ultrasound processes in the three aforementioned modalities: i) NPs pre-dispersion/exfoliation, ii) NPs dispersion/exfoliation with the polymer, and iii) NPs embedding on finished products.…”
Section: Embedding Of Nps On Finished Productsmentioning
confidence: 99%
“…Composites of starch and graphene derivatives have been developed and presented improvements in mechanical [7,19] and thermal [19,20] properties, as well as enhancements in electrical conductivity [20,21]. Favorable interactions and exfoliation of graphene sheets in the starch matrix explain these results.…”
Section: Introductionmentioning
confidence: 99%